1999
DOI: 10.1073/pnas.96.24.13732
|View full text |Cite
|
Sign up to set email alerts
|

Sequential mechanism of solubilization and refolding of stable protein aggregates by a bichaperone network

Abstract: A major activity of molecular chaperones is to prevent aggregation and refold misfolded proteins. However, when allowed to form, protein aggregates are refolded poorly by most chaperones. We show here that the sequential action of two Escherichia coli chaperone systems, ClpB and DnaK-DnaJ-GrpE, can efficiently solubilize excess amounts of protein aggregates and refold them into active proteins. Measurements of aggregate turbidity, Congo red, and 4,4-dianilino-1,1-binaphthyl-5,5-disulfonic acid binding, and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
526
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 554 publications
(554 citation statements)
references
References 19 publications
15
526
0
6
Order By: Relevance
“…We produced large aggregates of two substrates: glucose-6-phosphate dehydrogenase (G6PDH) and malate dehydrogenase (MDH) that can be reactivated by ClpB with the DnaK system of cochaperones. 8,12 We incubated the aggregates with ClpB in the absence and presence of different nucleotides and then determined the amount of ClpB bound to the aggregated particles (see Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We produced large aggregates of two substrates: glucose-6-phosphate dehydrogenase (G6PDH) and malate dehydrogenase (MDH) that can be reactivated by ClpB with the DnaK system of cochaperones. 8,12 We incubated the aggregates with ClpB in the absence and presence of different nucleotides and then determined the amount of ClpB bound to the aggregated particles (see Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…5 ClpB reactivates aggregated proteins in cooperation with the DnaK chaperone system. [6][7][8] The ClpB activity is linked to extraction of single polypeptides from aggregated particles and their forced unfolding by translocation through a narrow channel located at the center of the hexameric ring. 9 The substrate translocation by ClpB is driven by ATP hydrolysis and is analogous to the degradationpreceding unfolding/translocation of substrates by the proteasome and other ATP-dependent proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Using model proteins like β-galactosidase and firefly luciferase, many studies have addressed the role of the Hsp70 (DnaK)-Hsp40 (DnaJ)-Hsp110 (GrpE) system (also called KJE system) in re-activation of stress denatured proteins both in vitro and in vivo (Ben-Zvi et al, 2004;Goloubinoff et al, 1999;Pinto et al, 1991;Schroder et al, 1993). The refolding reaction is generally slow and is strictly dependent on ATP hydrolysis.…”
Section: Ii441 Chaperone Mediated Refolding and Disaggregationmentioning
confidence: 99%
“…Soon after the discovery of Hsp104 disaggregase in yeast, an orthologous protein called ClpB was shown to possess disaggregation activity in E. coli and in chloroplasts and mitochondria of higher eukaryotes . Several in vitro studies have shown that the Hsp104 or ClpB system alone has little or no disaggregation activity and requires collaboration with the Hsp70 system for effective disaggregation (Glover and Lindquist, 1998;Goloubinoff et al, 1999).…”
Section: Ii441 Chaperone Mediated Refolding and Disaggregationmentioning
confidence: 99%
“…In organisms and cellular compartments that also express Hsp100/ClpB homologues, the Hsp70-Hsp40 unfoldase chaperone systems benefit from a powerful synergic mechanism of forceful disaggregation that may act both upstream and downstream to the polypeptide unfoldase activity of Hsp70 chaperones (Glover and Lindquist 1998;Goloubinoff et al 1999;Weibezahn et al 2005). Thus, in the yeast cytoplasm, a large number of Hsp70-Hsp40 can collaborate with the ClpB-like (Hsp104) disaggregating co-chaperone to prevent the formation of misfolded species and even solubilizeresistant prions.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%